Prevalence, cessation, and geographical variation of smoking among middle-aged and elderly adults in China: A population-based study - Qingjia Zeng; Chongyang Zhang; Feiyu Su; Yanli Wan; Wen-jun Tu; Hongpu Hu (Tobacco Induced Diseases)
Introduction Smoking significantly burdens human health, contributing to an increasing incidence of mortality and morbidity. This study aims to explore the prevalence of smoking, cessation, and the association between various risk factors and smoking intensity measured in pack-years among Chinese adults.